Unlawful or illegal industrial actions by employees: Ground justifying dismissal - Ali Mohamed, Ashgar Ali (LexisNexis, 2016)
This paper discusses the issue of unlawful or illegal strike as a gross misconduct that warrants dismissal from employment and with reference to the Industrial Courts award.